Penerapan pendidikan karakter di perguruan tinggi - -, Sugiaryo - (Widya Wacana: Jurnal Ilmiah, 2010)
AbstractCharacter education is a value education, nature education, moral education, and character education aimed to develop the learner ability to provide good-bad decision, maintaining good things and ralizing virtue in daily life sincerely. Imperatively, university is one of character educational sites which interpreting nation`s character through three pillars of educational Three-deeds of University, they are education, research and public service, or through high educational unit of cultural development which reflected in daily activities in varied behavior constructs. Activities in educational sector includes curricular, cocurricular and also extracurricular. In curricular activity (in class,both real or virtual), the implementation of character education is implemented by holding an integrated approach on all subjects ( embedded approach). In co-curricular activity, they are out of class activities or out of related website directly on the subject matters, it must frequently held, such like activities in laboratories, studios, and also in public. While the extracurricular activity, they are educational unit activity with general in nature and not directly related with subject, such like talent, interest and creative innovative development activities. In research activity, the implementationof character education is held by the lecturer and or students by obeying the norms or rules /academic ethnics according to autonomous scientific principles. Public service is implemented by following institutional, scientific-deeds, deed-scientific, cooperation, sustainability, educative and development principles.Keyword : Implementation, character education, university